A Contemporary Medicolegal Analysis of Implanted Devices for Chronic Pain Management. (April 2017) - Abrecht, Christopher R.; Greenberg, Penny; Song, Ellen; Urman, Richard D.; Rathmell, James P.
Abstract : BACKGROUND: Analysis of closed malpractice claims allows the study of rare but serious complications and likely results in improved patient safety by raising awareness of such complications. Clinical studies and closed claims analyses have previously reported on the common complications associated with intrathecal drug delivery systems (IDDS) and spinal cord stimulators (SCS). This study provides a contemporary analysis of claims from within the past 10 years. METHODS: We performed a closed claims analysis for a period January 1, 2009 to December 31, 2013 for cases with pain medicine as the primary service. These cases were identified using the Controlled Risk Insurance Company (CRICO) Comparative Benchmarking System (CBS), a database containing more than 300, 000 malpractice claims from more than 400 academic and community institutions, representing approximately 30% of malpractice cases in the United States. The clinical narratives, which included medical files, claims files, depositions, and expert witness testimony, were reviewed by the authors, as were the CRICO coded variables, which included algorithmically determined contributing factors to the patient injury. RESULTS: Intrathecal drug delivery systems represented 17 of the closed claims; spinal cord stimulators represented 11 of the closed claims. The most common chronic pain diagnoses for which a device was implanted included failed back surgery syndrome and spasticity. The average total incurred for pain medicine claims was $166, 028. Damaging events included IDDS refill errors (eg, subcutaneous administration of medication, reprogramming errors), intraoperative nerve damage, and postoperative infection (eg, epidural abscess, meningitis). High-severity outcomes included nerve damage (eg, paraplegia) and death. Medium-severity outcomes included drug reactions (eg, respiratory arrest from opioid overdose) and the need for reoperation. For both IDDS and SCS, deficits in technical skill were the most common contributing factor to injury, followed by deficits in clinical judgment, communication, and documentation. CONCLUSIONS: Implanted devices used for pain management involve a significant risk of morbidity and mortality. Proper education of providers and patients is essential. Providers must acquire the technical skills required for the implantation and refilling of these devices and the clinical skills required for the identification and management of complications such as intrathecal granuloma. Proper patient selection and clear communication between the provider and the patient about these possible complications are of paramount importance.